The functional attributes of Peruvian (Kankolla and Blanca juli blend) and Northern quinoa (NQ94PT) flours and protein isolates, and their protein quality. (February 2020) - Shi, Dai; Fidelis, Marília; Ren, Yikai; Stone, Andrea K.; Ai, Yongfeng; Nickerson, Michael T.
Graphical abstract: Highlights: Properties of Peruvian (PQ) and Northern (NQ) flours and isolates were examined. Water and oil binding properties of PQ and NQ flours were similar. PQ and NQ isolates had much higher water and oil binding properties than flours. Protein solubility of the isolates was minimum at pH 5, but higher at other pHs. Protein quality was greater in the isolates than the flours. Abstract: The overall goal of this research was to examine differences in the composition, functionality and protein quality between Peruvian (PQ) and Northern (NQ) quinoa flours, and their isolates prepared by alkaline extraction/isoelectric precipitation. In the case of the flours, PQ and NQ were comprised of 13.6% and 12.8% protein, respectively. Water hydration (mean value = 1.65 g/g) and oil holding capacities (mean value = 1.75 g/g) of both flours were similar, whereas solubility increased from pH 3 to 7 for both flours, but was higher for PQ. Flours were non-foaming at pH 3, but showed increased foam capacity as the pH increased from 5 to 7, but was higher for PQ. Similar foam stability was found for both flours. Emulsion stability (ES) was similar for both flours, and increased from pH 3 to pH 5/7. In the case of the isolates, water hydration capacity was greater for PQ (4.75 g/g) than NQ (2.85 g/g), whereas oil holding capacity was similar (mean value = 8.6 g/g). For both isolates, solubility was minimum at pH 5.0 and maximum at pH 3/7, with NQ being higher. Isolates showed 2–3 times the foam capacity as flours, the magnitude of which was cultivar and pH dependent. Foam stability was lower at pH 5 than at pH 3/7, whereas ES followed a similar pH effect. Tyrosine and phenylalanine were limiting in both flours, whereas threonine was limiting in both isolates. In vitro protein digestibility corrected amino acid scores for the flours was higher for PQ (56.8%) than NQ (47.7%); however, the reverse was observed for the isolates (NQ, 62.1%; PQ, 58.9%).